Toddler nutritional status based on feeding practices in an urban high density: A cross-sectional study - Ari Indra Susanti; Putri Argi Larasati; Ariyati Mandiri; Insi Farisa Desy Arya; Tisnasari Hafsah; Dida Akhmad Gurnida (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: The prevalence of stunting in Indonesia remains a significant challenge in public health development, with a national stunting rate of 21.5% in 2023, higher than the WHO target (<20%). One important factor influencing the nutritional status of toddlers is feeding practices, particularly in urban communities such as Babakan Ciparay, Bandung. Objective: This study aimed to analyze the relationship between feeding practices and the nutritional status of toddlers aged 24–59 months. Methods: This study used a cross-sectional design and was conducted from April to July 2024 among 47 mothers with toddlers selected through purposive sampling. Data were collected based on anthropometric measurements of toddlers determine nutritional status (weight/age, height/age, weight/height) at Posyandu. Data on feeding practices were collected using a questionnaire. Data were analyzed  univariately and bivariately using the Chi-Square test (weight/age, height/age) and Fisher's Exact test (weight/height). Results: The results showed that there was a significant relationship between nutritional status of weight-for-age (BB/U) and type of food and between nutritional status of height-for-age (TB/U) and feeding method (p-value <0.05). However, no significant associations were found between amount of food and meal schedule and toddlers’ nutritional status based on BB/U, TB/U, or weight-for-height (BB/TB) (p-value>0.05). Conclusion: The quality of food type and feeding methods play important roles in toddlers’ nutritional status of toddlers, particularly in terms to BB/U and TB/U. Therefore, these findings can be used as a basis for planning family-based nutrition.